«Venire» vs «andare» - distinzioni pragmatiche - Drzymała, Piot (Studia Romanica Posnaniensia, 2003)
The paper presents an explication of semantic differences between the two Italian verbs, venire and andare, in a pragmatic perspective, i.e. referring to the presupposition. A distinction is initially made between presuppositions, on the one hand, inherent in some lexical items, syntactic structures and prosodic features and, on the other, those "generated" by specific speech acts. The presuppositions inherent in both of these verbs permit an exhaustive contrastive description of their occurrences, even in non-deictic uses and transpositions from direct to indirect speech, which constitutes a contribution to the didactics of Italian as a foreign language.